Identifikasi perekonomian kabupaten kerinci - Hodijah, Siti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
Abstrak This research entitled â€œEconomic Identification Kerinci Regency period 2000-2007â€. Purpose of this research is to know the economic sectors in the base or leading and to know determine inter-regional specialization and sector specialization of excellent base among Regency/City in Jambi Province with Kerinci Regency. From LQ calculation can be known Kerinci Regency have a base sector in sector: sector Agriculture, Livestock, Forestry & Fishery, sector of electricity, Gas & Water Utilities, sector Transportation and Communications, Finance, sector Real Estate & Business Services and sector services.